Differentially expressed proteins underlying childhood cortical dysplasia with epilepsy identified by iTRAQ proteomic profiling - Qin, Lu (PLoS One, 2017)
Cortical dysplasia accounts for at least 14% of epilepsy cases, and is mostly seen in children. However, the understanding of molecular mechanisms and pathogenesis underlying cortical dysplasia is limited. The aim of this cross-sectional study is to identify potential key molecules in the mechanisms of cortical dysplasia by screening the proteins expressed in brain tissues of childhood cortical dysplasia patients with epilepsy using isobaric tags for relative and absolute quantitation-based tandem mass spectrometry compared to controls, and several differentially expressed proteins that are not reported to be associated with cortical dysplasia previously were selected for validation using real-time polymerase chain reaction, immunoblotting and immunohistochemistry. 153 out of 3340 proteins were identified differentially expressed between childhood cortical dysplasia patients and controls. And FSCN1, CRMP1, NDRG1, DPYSL5, MAP4, and FABP3 were selected for validation and identified to be increased in childhood cortical dysplasia patients, while PRDX6 and PSAP were identified decreased. This is the first report on differentially expressed proteins in childhood cortical dysplasia. We identified differential expression of FSCN1, CRMP1, NDRG1, DPYSL5, MAP4, FABP3, PRDX6 and PSAP in childhood cortical dysplasia patients, these proteins are involved in various processes and have various function. These results may provide new directions or targets for the research of childhood cortical dysplasia, and may be helpful in revealing molecular mechanisms and pathogenesis and/or pathophysiology of childhood cortical dysplasia if further investigated.